2019
DOI: 10.1038/s41598-018-36298-z
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Activates Vagal Control of Hyperglycemia and Inflammation in Fasted Mice

Abstract: Sepsis is a leading cause of death in hospitalized patients. Many experimental treatments may have failed in clinical trials for sepsis, in part, because they focused on immune responses of healthy animals that did not mimic the metabolic settings of septic patients. Epidemiological studies show an association between metabolic and immune alterations and over 1/3 of septic patients are diabetic, but the mechanism linking these systems is unknown. Here, we report that metabolic fasting increased systemic inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Also, IL-10 that is produced by macrophages and T-cells is a potent inhibitor of macrophagederived inflammatory cytokines synthesis [54]. As pathogen activates the innate immune response through activation of the NF-B signaling pathways which is essential to the generations of inflammatory cytokines as TNF-αand interleukins which played a crucial role in fighting infection [55].In the current study, E.coli infected group showed a significant increase in serum level of TNF-α. and IL-10.…”
Section: Discussionmentioning
confidence: 56%
“…Also, IL-10 that is produced by macrophages and T-cells is a potent inhibitor of macrophagederived inflammatory cytokines synthesis [54]. As pathogen activates the innate immune response through activation of the NF-B signaling pathways which is essential to the generations of inflammatory cytokines as TNF-αand interleukins which played a crucial role in fighting infection [55].In the current study, E.coli infected group showed a significant increase in serum level of TNF-α. and IL-10.…”
Section: Discussionmentioning
confidence: 56%
“…Likewise, a recent study indicated that efferent vagal stimulation attenuates hyperglycemia in endotoxemia by inducing insulin in fasted mice [35] . However, while combined afferent and efferent cervical VNS impaired glucose tolerance and inhibited glucose-induced insulin secretion in conscious rats [12] .…”
Section: Discussionmentioning
confidence: 98%
“…EA activates mechanisms that have physiologic limitations, and they are ineffective in patients with multiple comorbidities ( 57 , 58 ). One typical example is that EA on ST36 improves organ function and survival in experimental sepsis by inducing dopamine production in the adrenal glands ( 49 , 59 ). However, many septic patients have adrenal insufficiency, and thus they render insufficient dopamine production for EA to induce significant effects ( 49 , 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%